Acoustic calculation of process pipelines of a compressor station for assessing low-frequency pressure pulsations in dead-end branches - Alexander S. Schreder; Oleg A. Kurasov; Petr V. Burkov; Alexey N. Gavrilin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The gas industry cannot be imagined without main gas pipelines, which are necessary to provide suppliers with the declared quantities of gas. To fulfill contractual obligations, compressor stations with high-flow compressor units are used. In order to ensure reliable operation and avoid premature failure of process equipment, periodic diagnostic work is carried out. Such measures allow increasing the service life of objects, but due to high static stresses and the occurrence of intense dynamic loads characteristic of process pipelines, this is not a sufficient condition for identifying potentially dangerous areas. In this regard, recently, engineering tools for calculating dynamic processes have been increasingly used to help solve such complex problems in order to study these processes in real systems and operating modes. Methods. Engineering analysis products to calculate the amplification of acoustic vibrations in dead-end branches of the technological piping of a compressor station. Results and conclusions. The authors have calculated the technological piping to assess the acoustic vibrations, the natural frequencies of vibrations of dead-end clarifications and the critical speeds, at which these vibrations occur. The paper introduces the results of the acoustic calculation carried out in the ANSYS Workbench software. According to these results the authors determined the pulsation amplifications in the dead-end branches, which are relatively large and can be the cause of high low-frequency vibrations.